Critical behavior in porous media flow. (6th June 2017) - Moura, M.; Måløy, K. J.; Toussaint, R.
Abstract: The intermittent burst dynamics during the slow drainage of a porous medium is studied experimentally. We have shown that this system satisfies a set of conditions known to be true for critical systems, such as intermittent activity with bursts extending over several time and length scales, self-similar macroscopic fractal structure and power spectrum. Additionally, we have verified a theoretically predicted scaling for the burst size distribution, previously assessed via numerical simulations. The observation of power spectra is new for porous media flows and, for specific boundary conditions, we notice the occurrence of a transition from 1/ f to 1/ f 2 scaling. An analytically integrable mathematical framework was employed to explain this behavior.